Prevalence of asthma and allergic disorders in school children of Karachi - Samoo, Urooj Gul; Ehsan, Shaista (International Journal of Contemporary Pediatrics, 2021)
Background: The aim of the study was to determine the frequency of asthma and allergic diseases and to identify the associated risk factors in school-aged children of Karachi. Methods: This prospective, cross-sectional study was conducted from August 2019 to January 2020 on school-aged children (4-15 years) of Karachi. Non-probability purposive sampling technique was used, data was analyzed using SPSS version 20. Results: The prevalence of allergic rhinitis and eczema in the study population was 22.1%, asthma 14% and 34% had a history of wheezing in the last 12 months. Food allergy was present in 15.5% of the study population. The predisposing factors were exposure to dust in 32.6%, passive smoking in 30.8%, perfume smell in 27.3% and the presence of pets in the house in 23.2%. Male gender and maternal asthma were significantly associated with the development of these allergic disorders in children (p=0.033). Conclusions: There is a high prevalence of allergic disorders and asthma amongst the school children of Karachi. Environmental factors such as exposure to dust and passive smoking are significant predisposing factors. There is an urgent need to conduct further epidemiological studies to identify high-risk groups and key modifiable factors.